Ischemia-Modified Albumin, a Novel Predictive Marker of In-Hospital Mortality in Acute Aortic Dissection Patients - Yang, Guifang; Zhou, Yang; He, Huaping; Pan, Xiaogao; Chai, Xiangping (Frontiers in Physiology, 2019)
Background: This work explored the prognostic prediction capabilities of ischemia-modified albumin (IMA) in patients suffering from acute aortic dissection (AAD). Methods: We conducted a retrospective analysis using electronic health records. This study included AAD patients admitted to the Second Xiangya Hospital of Central South University from Jan 2015 to Dec 2018 in ≤ 24 hours from the onset of symptoms to hospital admission. The levels of IMA were recorded upon admittance and the final was the all-cause mortality during hospitalization. Results: This study enrolled 731 AAD patients. Among who, 160 passed away in the course of medication while 571 of them survived. Those who passed away exhibited higher levels of IMA (94.35 ± 26.84 vs. 69.14 ± 14.70, p < 0.001) than the survivors. Following the adjustment confounders, the fully-adjusted model showed IMA to be an independent forecastor for in-hospital mortality for AAD patients (OR 1.10, 95% CI 1.08 – 1.13, p < 0.001). Analysis based on receiver operating characteristic (ROC) revealed that 79.35 u/ml was the best threshold of IMA level. The area under the curve based on this IMA level was 0.854 (95% CI 0.822 – 0.898) while the specificity and sensitivity to anticipate in-hospital death were 84.8% and 80.6%, respectively. Conclusions: Admission IMA was an independent forecastor for in-hospital mortality among people suffering from AAD.